(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics and to evaluate the treatment outcomes of distal ureteral stones managed by retrograde ureteroscopic lithotripsy using Holmium laser energy. Materials and methods: A prospective descriptive study was conducted on 35 patients diagnosed with distal ureteral stones, treated with retrograde ureteroscopic lithotripsy at the Department of Surgery, Huong Son District Health Center (Ha Tinh province), from March 2024 to March 2026. Result: The mean age was 55.11 ± 12.94 years (range: 33–82), with a male-to-female ratio of 2:1. A history of urinary stones was present in 51.4% of patients, with a mean symptom duration of 8.51 days. The most common presenting symptom was renal colic (77.1%). On ultrasound, grade 1 hydronephrosis was most frequent (77.1%). Stones were located on the right and left sides in 16 and 19 cases, respectively. Stone size was predominantly 5–10 mm (94%). Impacted stones at the ureteral orifice were observed in 60% of cases. The mean operative time was 20 ± 8.15 minutes. No intraoperative or postoperative complications were recorded. The mean hospital stay was 7.1 ± 2.4 days. Conclusion: Retrograde ureteroscopic lithotripsy using Holmium laser is a safe and effective method for treating distal ureteral stones at Huong Son District Health Center, Ha Tinh province.